Claws! - Stine, R. L. (New York : Scholastic., 2012)
Mickey and Amanda are babysitting their neighbor's cat Bella, but Bella escapes, is hit by a truck and is killed. Mickey feels awful, but Amanda decides they should just replace the cat, and since the clerk won't sell Bella's look-alike to them, they decide to steal her.
Keywords: Cats -- Juvenile fiction; Pet sitting -- Juvenile fiction; Horror fiction